Eastward of Good Hope : Early America in a Dangerous World - Morrison, Dane Anthony (Book collections on Project MUSE., 2021)
"Reexamining Yankee "voyages of commerce and discovery" into distant seas in the decades after the War of Independence, this book reveals how "news from the East" carried in ships logs and mariners' news reports, journals, and correspondence shaped Americans' understanding of the world as a map of dangerous and incoherent sites. Focusing on four representative arenas-the Ottoman Empire, China, India, and the Great South Sea-and drawing on recent scholarship in global ethnohistory, the author recounts how reports of cannibal encounters, shipboard massacres, shipwrecks, tropical fever, and other tragedies in distant seas led Americans to imagine each region as a distinct set of threats to their republic"--